Robustness and Linear Contracts - Carroll, Gabriel (American Economic Review, 2015)
We consider a moral hazard problem where the principal is uncertain as to what the agent can and cannot do: she knows some actions available to the agent, but other, unknown actions may also exist. The principal demands robustness, evaluating possible contracts by their worst-case performance, over unknown actions the agent might potentially take. The model assumes risk-neutrality and limited liability, and no other functional form assumptions. Very generally, the optimal contract is linear. The model thus offers a new explanation for linear contracts in practice. It also introduces a flexible modeling approach for moral hazard under nonquantifiable uncertainty. (JEL D81, D82, D86)